2019
DOI: 10.1055/s-0039-1688537
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Lower Extremity Lymphedema: A Comprehensive Review

Abstract: Lymphedema refers to the accumulation of protein-rich fluid in the interstitial spaces. This can occur secondary to congenital malformation of the lymphatic channels or nodes or as a result of an insult that damages appropriately formed channels and nodes. Stagnant, protein-rich lymph initiates an inflammatory response that leads to adipocyte proliferation, fibrous tissue deposition, and increased susceptibility to infections. The end result is permanent disfigurement and dermal changes. Early and accurate dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 68 publications
(73 reference statements)
0
54
0
Order By: Relevance
“…43 Compression therapy should be initiated one month postsurgery and patients should be follow up each 3 months postoperatively to assess volume reduction until maintenance of limb size is achieved with daytime therapy for 3 consecutive months. 94 Our systematic review found that the largest reduction rates achieved after LVA for LEL ranged between 51.1 and 63.8%, with better results presented in early stages of lymphedema, and that almost all studies reported a decrease in episodes of infection. Patients' satisfaction after LVA has been also evaluated.…”
Section: Discussionmentioning
confidence: 81%
“…43 Compression therapy should be initiated one month postsurgery and patients should be follow up each 3 months postoperatively to assess volume reduction until maintenance of limb size is achieved with daytime therapy for 3 consecutive months. 94 Our systematic review found that the largest reduction rates achieved after LVA for LEL ranged between 51.1 and 63.8%, with better results presented in early stages of lymphedema, and that almost all studies reported a decrease in episodes of infection. Patients' satisfaction after LVA has been also evaluated.…”
Section: Discussionmentioning
confidence: 81%
“…However, there is new evidence that early diagnosis allows proactive management of the disorder, using Lymphatic Venous Anastomosis and Vascularized Lymph Node Transfer. These surgical interventions can slow disease progression and improve the lymph drainage through the preservation of the residual functioning lymphatics 22,27 . VLNT is utilized for hypoplastic LE, 23,28 and LVA is the technique of choice in patients with hyperplastic lymphatic pattern and dilated lymphatic vessels 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The following MR findings were recorded for each patient, regardless of the number of limbs involved: laterality of the swelling (unilateral/bilateral) and its symmetry, the presence of the honeycomb pattern 17,21 visible as trabecular/reticular structures with enlarged fat pockets in the subcutaneous fat (Fig. 2); thickening of the dermis (dermis thickness >2 mm); abnormalities in the muscle compartment, such as impaired trophism or altered signal; the number of inguinal lymph nodes; the appearance of iliac lymphatic trunks 22,23 classified as hypoplastic, if <3 lymphatic trunks were recognizable, normal, when 3–6 lymphatic trunks were visible, or hyperplastic, if >6 lymphatic trunks were present or if their caliber was >3 mm; and dilatation of distal lymphatic vessels (diameter >2 mm) 17,18 …”
Section: Methodsmentioning
confidence: 99%
“…The amount of fluid accumulated can reach up to 5–15 L [ 7 ]. It requires continuous treatment including meticulous care on behalf of the patient, non-invasive therapy options, such as physical therapy, and surgery [ 8 , 9 ]. However, no definite cure is currently available.…”
Section: Introductionmentioning
confidence: 99%